Development of a Vibration Powered Micro Generator and its Application to Harvest the Vibration Energy of the KRI KKP-811’s Engine - Harus L.G.; Wiwiek Hendrowati; Rahmat Susanto (Jurnal Teknik Mesin (Sinta 3), 2010)
Vibration energy harvesting has been receiving a considerable amount of interest as a means of powering wireless sensors and low-power devices. In this paper, an energy harvester is presented to convert ambient mechanical vibration into electrical energy employing magnetoelectric generator. The harvester uses single magnet-spring attached on the coil. When the harvester is excited, the magnet moves relative to the coil, undergoes magnetic field variations and produces a power output. To obtain a maximum power output, the mass of magnet is varied. The magnetoelectric generator with various masses of magnets was tested by a harmonic exciter with various frequencies and amplitudes. The one with maximum power output was then applied to harvest the ambient vibration energy of KRI KKP-811’s Engine. The results show that this prototype can harvest maximum energy of 2μW when it is placed at the base/foundation of the engine.